Examining Ownership Equity as a Psychological Factor on Tourism Business Failure Forecasting - Korol, Tomasz; Spyridou, Anastasia (Frontiers in Psychology, 2020)
This paper examines ownership equity as a predictor of future business failure within the tourism and hospitality sectors. The main goals of this study were to examine which ratios are the most important for a tourism business failure forecasting model and how significant is the “total percentage of equity ownership by company directors” ratio compared to other ratios associated with the probability of bankruptcy. A Stepwise Weight Assessment Ratio Analysis (SWARA) was applied and twelve (12) tourism bankruptcy experts evaluated key ratios. Total percentage of equity ownership by company directors is considered a psychological factor and it was identified as the fourth most important ratio for a business failure forecasting model. Academicians and practitioners can use the findings of this study whenever developing a forecasting model for tourism and hospitality enterprises.